The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.neuroscience.2007.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Injection of adjuvant but not acidic saline into craniofacial muscle evokes nociceptive behaviors and neuropeptide expression

Abstract: Craniofacial muscle pain including muscular temporomandibular disorders accounts for a substantial portion of all pain perceived in the head and neck region. In spite of its high clinical prevalence, the mechanisms of chronic craniofacial muscle pain are not well understood. Injection of acidic saline into rodent hindlimb muscles produces pathologies which resemble muscular pathologies in chronic pain patients. Here we investigated whether analogous transformations occur following repeated injections of acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 60 publications
3
40
1
3
Order By: Relevance
“…As the use of intramuscular acidic saline injections increases, reports are emerging that pH 4.0 saline injection does not always generate demonstrable hypersensitivity. For example, a recent study by Ambalavanar et al3 reported that pH 4.0 saline injection into the masseter muscle failed to induce nociceptive behavioral responses. This has led some to question the reliability of acidic saline to induce hyperalgesia, but this result could also be explained simply by the inherent differences in various muscles to acidic saline injection (masseter versus gastrocnemius).…”
Section: Discussionmentioning
confidence: 99%
“…As the use of intramuscular acidic saline injections increases, reports are emerging that pH 4.0 saline injection does not always generate demonstrable hypersensitivity. For example, a recent study by Ambalavanar et al3 reported that pH 4.0 saline injection into the masseter muscle failed to induce nociceptive behavioral responses. This has led some to question the reliability of acidic saline to induce hyperalgesia, but this result could also be explained simply by the inherent differences in various muscles to acidic saline injection (masseter versus gastrocnemius).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gerwin et al (2004) hypothesized that CGRP intensifies the response to excess ACh at the nerve terminal by enhancing ACh receptor activity and synthesis, supporting the role of neuropeptides in the MTrP pathophysiology. On the other hand, a study by Ambalavanar et al (2007) found that CGRP expression in the rat is muscle-specific; e.g. craniofacial muscles react differently to noxious stimuli than hindlimb muscles.…”
Section: Neuropeptidesmentioning
confidence: 98%
“…Inflammatory models of muscle pain involve injecting an irritating compound (mustard oil, carrageenan, complete freund's adjuvant, formalin, etc.) into the muscle, which triggers a robust inflammatory response [4;30;52;66;72;152] designed to mimic myositis and muscle strains in humans [115]. These compounds result in decreased mechanical withdrawal thresholds of muscle and paw, enhanced avoidance to noxious stimuli (PEAP), and decreased voluntary activity [16;79;80;149;152;175;196].…”
Section: Animal Models Of Diseasementioning
confidence: 99%